The new illustrated science and invention encyclopedia the new how it works. (Westport, Conn. H.S. Stuttman, 1987)
An alphabetical encyclopedia covering all aspects of science, the physical world, mechanics, and engineering.
"Newly revised and updated How it works"--Reader's guide.
Keywords: Science -- Encyclopedias; Engineering -- Encyclopedias